2013
DOI: 10.13109/prkk.2013.62.8.570
|View full text |Cite
|
Sign up to set email alerts
|

Schulabsentismus in Deutschland - Die Prävalenz von entschuldigten und unentschuldigten Fehlzeiten und ihre Korrelation mit emotionalen und Verhaltensauffälligkeiten

Abstract: Summary School Absenteeism in Germany: Prevalence of Excused and Unexcused Absenteeism and its Correlation with Emotional and Behavioural ProblemsData about the prevalence of school absenteeism and its correlation with emotional and behavioural problems in Germany is scarce, in particular regarding excused absenteeism. This study aims to close the gap by examining a sample of 2,679 pupils attending the different types of secondary school (Hauptschule, Realschule, Gymnasium), who participated in a clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…The presence of psychosocial problems was confirmed by the significantly higher mean scores of SDQ total difficulties scales in the study group. Lenzen already demonstrated that medical absenteeism is positively associated with emotional and behavioural problems [43]. The nature of the problems appears to be diverse, when looked at from a biopsychosocial perspective: psychosocial problems, physical complaints, sleeping difficulties and lifestyle problems can be the underlying reasons for medical absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of psychosocial problems was confirmed by the significantly higher mean scores of SDQ total difficulties scales in the study group. Lenzen already demonstrated that medical absenteeism is positively associated with emotional and behavioural problems [43]. The nature of the problems appears to be diverse, when looked at from a biopsychosocial perspective: psychosocial problems, physical complaints, sleeping difficulties and lifestyle problems can be the underlying reasons for medical absenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates on school absenteeism as reported in literature are not directly comparable internationally, due to inconsistent use of parameters for school absenteeism. Nowadays, figures at the national level show that medical absenteeism occurs approximately twice as often as truancy [ 22 24 ]. In the Netherlands in 2002 medical absenteeism was more prevalent in pre-vocational secondary education than in the other two tracks in secondary education (senior general secondary education and pre-university education): 4 v. 3.7 and 3.4 % [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medizinische Screening-Verfahren im Selbstbericht erreichen ähnliche Werte, auch wenn diese nicht direkt vergleichbar sind, da in unserer Studie zwei Gruppen an den Extremen der Verteilung verglichen werden -Klinikschülerinnen und -schüler mit abgesicherter psychiatrischer Diagnose und Regelschülerinnen und -schüler ohne SDQ-Auffälligkeit. So erreicht beispielsweise der SDQ-Selbstbericht ein AUC von .84 (Becker et al, 2004) (Al-Mouhtasseb, Hebebrand & Knollmann, 2009;Egger, Costello & Angold, 2003;Lenzen et al, 2013). Im schulischen Bereich ist dieses Ergebnis dennoch beachtenswert, da der Fokus von Lehrkräften stark auf die Erfassung schulischer Leistungen und das Arbeitsverhalten von Schülerinnen und Schülern ausgerichtet ist und ihnen die Beurteilung nicht-leistungsbezogener Merkmale wie z.…”
Section: Diskussion Zusammenfassung Und Einordnungunclassified